Secret selves : confession and same-sex desire in Victorian autobiography - Buckton, Oliver S. (University of North Carolina Press, 1998)
Focusing on the representation of same-sex desire in Victorian autobiographical writing, Oliver Buckton offers significant new readings of works by such influential 19th-century writers as Edward Carpenter, John Henry Newman, John Addington Symonds, and, in an epilogue, E.M. Forster, and reveals the "confessional" elements of their writings.
Keywords: Englisch, ...; English prose literature -- 19th century -- History and criticism.; Autobiography.; Male authors, English -- 19th century -- Biography -- History and criticism.; Homosexuality and literature -- Great Britain -- History -- 19th century.; Gay men -- Great Britain -- Biography -- History and criticism.; Gay men's writings, English -- History and criticism.; Great Britain -- History -- Victoria, 1837-1901 -- Historiography.; Confession in literature.; Desire in literature.; Authors, English -- 19th century -- Biography -- History and criticism.; Homosexuality and literature -- England -- History -- 19th century.; Gay men -- England -- Biography -- History and criticism.; Autobiographies as Topic.; Prose anglaise -- 19e siècle -- Histoire et critique.; Autobiographie.; Écrivains anglais -- 19e siècle -- Biographies -- Histoire et critique.; Homosexualité et littérature -- Angleterre -- Histoire -- 19e siècle.; Homosexuels masculins -- Angleterre -- Biographies -- Histoire et critique.; Écrits d'homosexuels anglais -- Histoire et critique.; Confession dans la littérature.; Désir dans la littérature.; Grande-Bretagne -- Histoire -- 1837-1901 (Vic.) -- Historiographie.; Homosexualité et littérature -- Grande-Bretagne -- Histoire -- 19e siècle.; Homosexuels masculins -- Grande-Bretagne -- Biographies -- Histoire et critique.; Grande-Bretagne -- Histoire -- 1837-1901 (Victoria) -- Historiographie.; autobiography (genre); LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; LITERARY CRITICISM -- Gay & Lesbian.; Gay men; Autobiography; Confession in literature; Desire in literature; English prose literature; Gay men -- Biography; Gay men's writings, English; Historiography; Homosexuality and literature; Male authors, English -- Biography; England; Great Britain; Authors, English -- Biography; Autobiografieën.; Engels.; Homoseksuelen.; Bekentenis.; Wensen.; Autobiografie; Homosexualität; Schriftsteller; Großbritannien; Geschichte 1845-1960.; Englisch.; 1800-1901; Autobiographies; Criticism, interpretation, etc.; History; autobiographies (literary works); Autobiographies.